Functional characterization of eight rare missense CYP1B1 variants involved in congenital glaucoma and their association with null genotypes. (6th April 2016) - Medina‐Trillo, Cristina; Ferre‐Fernández, Jesús‐José; Aroca‐Aguilar, José‐Daniel; Bonet‐Fernández, Juan‐Manuel; Escribano, Julio
Abstract: Purpose: To evaluate the function of eight missense CYP1B1 single nucleotide variants (SNVs) previously identified in patients with primary congenital glaucoma (PCG). Methods: The eight variants were obtained by site‐directed mutagenesis and transiently expressed in human embryonic kidney 293‐T (HEK‐293T) cells. The catalytic activity, protein stability and subcellular localization of the different recombinant CYP1B1 variants were assessed in this cell line. Results: Six of the mutant CYP1B1 proteins (p.L89P, p.A106D, p.R390S, p.P437L, p.C470Y and S485F) showed catalytic activity values ranging from 0% to 4% of those of the wild‐type protein and were considered null variants. The activity values of the two remaining variants (p.F123L and p.A237E) were close to 20% of that of the wild‐type enzyme and were classified as hypomorphic variants. Reduced protein stability contributed partially to the decreased catalytic activity of two of the mutant enzymes (p.L89P and p.A106D). None of the CYP1B1 variants showed intracellular aggregation and they all displayed a normal subcellular localization in the endoplasmic reticulum, suggesting that they had folded into a wild‐type‐like structure. The enzymatic activity associated with the different genotypes in which these CYP1B1 variants were present was estimated to range from 0% to 10% of that of the wild‐type genotype. Conclusion: These results confirm the pathogenicity of the analysed missense CYP1B1 variants and further support the concept that either absent or very low CYP1B1 activity levels are the primary molecular defect involved in PCG pathogenesis.